KRONOLOGI PENCIPTAAN KOMPOSISI KARAWITAN MIRATDANA - I Ketut Saba (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2014)
Art work creation, one of which is music composition, can occur because a variety of internal and external motives. This music composition entitled Miratdana is created because of concern with various social agitations among a group of people making the society restless as shown in printed and electronic media. For example: murder, robbery, corruption and the similar deeds resulting in other’s loss of both property and even life. Music composition is one means of musing that is expected to bring back the people awareness, because within it there are many song verses of life speech. The person, who had committed crime and tended to be anarchic, in my opinion, has forgotten a variety of life enjoyment the God had bestowed as the universe creator. In Balinese the similar thing is called Miratdana.Keywords: social agitation, music composition, awareness